Theophylline for Prevention of Kidney Dysfunction in Neonates With Severe Asphyxia (Iranian Journal of Kidney Diseases, 2009)
Introduction. Recent studies have suggested theophylline for prevention of kidney dysfunction in asphyxia. This study was designed to determine whether theophylline could prevent or ameliorate kidney dysfunction in term neonates with perinatal asphyxia.Materials and Methods. We assigned 36 severely asphyxiated term infants (Apgar score ? 5) into 2 groups to receive intravenously a single dose of either theophylline (5mg/kg; n =17) or placebo (n =19) during their first 60 minutes of life. The 24-hour fluid intake and the urine volumes were recorded during the 1st, 3rd, and 5th days of life. Severe kidney dysfunction was defined as a serum creatinine level elevated up to more than 1.50 mg/dL for at least 2 consecutive days after a fluid challenge, or 0.3-mg/dL/d rising levels of serum creatinine.Results. On the 1st day, the 24-hour fluid balance was more positive in infants receiving placebo compared to infants receiving theophylline. Over the next few days, the change in fluid balance favored the theophylline group. Significantly higher serum creatinine values were recorded in the placebo group on the 3rd day. Severe kidney dysfunction was present in 2 infants of the theophylline group (11.7. %) and in 8 (42.1%) of the controls. The glomerular filtration rate was markedly increased in the theophylline group. There was no difference in the severity of the asphyxia between the infants of the theophylline and control groups.Conclusions. Prophylactic theophylline, given early after birth, has beneficial effects on reducing kidney dysfunction in neonates with asphyxia.